The PENGEMBANGAN EKOWISATA DI SITU GEDE DITINJAU DARI MOTIVASI DAN PREFERENSI PENGUNJUNG - Melewanto Patabang; Dyah Prabandari; Occy Bonanza; Natasha Indah Rahmani; Ira Resmayasari; Kania S Rahayu; Hardjanto (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2024)
Situ Gede offers various ecotourism resources, such as research forests, Situ Gede Lake, natural landscapes, and diverse types of flora and fauna that attract tourists. To increase the number of visitors, these resources need to be developed effectively. As tourists visiting Situ Gede have different characteristics, motivations, and preferences, these differences must be studied to develop ecotourism in Situ Gede. The research aims to identify the motivation, preferences, and evaluations of visitors that can be used to develop ecotourism in Situ Gede. The study uses a 1-4 Likert scale, and data analysis involves descriptive methods, calculating standard deviation values, and Pearson Chi-Square analysis. The research findings indicate that the primary motivation for respondents to visit is physical. Three tourism activities are influenced by age, namely meeting friends, being with family and attending meetings, and culinary tourism. The activities around the lake that are most popular with visitors are taking selfies, enjoying the lake's beauty, and having a picnic in a natural setting. The most popular activities in the Research Forest are relaxing and enjoying the forest atmosphere, observing the variety of plants there, and taking photos with a forest background.